Electrostatic spinning solution of dried ginger essential oil nanofiber mask, nanofiber mask and preparation method of nanofiber mask

Dry ginger essential oil nanofiber mask prepared through electrospinning technology uses polyvinyl alcohol, hyaluronic acid and dry ginger essential oil inclusions to solve the problem of poor stability of dry ginger essential oil, achieving high hydrophilicity and moisturizing properties. Nanofiber mask, popular and applied.

CN119221201APending Publication Date: 2024-12-31CHENGDU UNIV OF TRADITIONAL CHINESE MEDICINE
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411202507.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-29
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Dried ginger essential oil has limited its widespread use in beauty and skin care due to its poor water solubility, high volatility and poor stability.

Method used

Using polyvinyl alcohol, hyaluronic acid and dried ginger essential oil inclusion compound and water as raw materials, nanofiber masks are prepared through electrospinning technology to control the inclusion rate of dried ginger essential oil, improve the stability and utilization rate of the inclusion compound, and form A nanofiber mask with smooth surface and tight structure.

Benefits of technology

It achieves good hydrophilicity and moisturizing properties of nanofiber masks, improves safety and moisturizing rates, and is easy to promote and apply.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119221201A_ABST
    Figure CN119221201A_ABST
Patent Text Reader

Abstract

The invention provides an electrostatic spinning solution of a rhizoma zingiberis essential oil nanofiber facial mask, the nanofiber facial mask and a preparation method of the nanofiber facial mask. Polyvinyl alcohol, hyaluronic acid, a rhizoma zingiberis essential oil clathrate compound and water are used as raw materials, and the inclusion rate of the rhizoma zingiberis essential oil clathrate compound and the proportion of all the raw materials are controlled; the nanofiber mask loaded with the rhizoma zingiberis essential oil clathrate compound and prepared by adopting the electrostatic spinning solution is smooth in surface, compact in structure, good in hydrophilic performance and wettability, high in safety and moisture retention and convenient to popularize and apply.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of preparation of dried ginger essential oil facial masks, and in particular to an electrostatic spinning solution of a dried ginger essential oil nanofiber facial mask, a nanofiber facial mask and a preparation method thereof. Background Art

[0002] Natural, safe, green and environmentally friendly are the current trends in cosmetics in the world. Plant extracts, especially Chinese herbal extracts, are favored by researchers in the fields of skin care products and health care products because of their natural origin, multiple biological activities and low irritation. Dried ginger comes from the dried rhizome of ginger (Zingiber officinale Rosc.), a traditional "dual-purpose medicine and food" medicinal material with a long history of medicinal use and beauty and skin care. In the Tang Dynasty's "Prescriptions Worth a Thousand Gold" and "Winged Prescriptions of a Thousand Gold", dried ginger was already the most commonly used Chinese herbal medicine in the anti-aging prescription and a food-like herbal medicine.

[0003] As one of the main active ingredients of dried ginger, the role of dried ginger essential oil in beauty and skin care cannot be ignored. Unlike general natural extracts, essential oils not only contain a variety of active ingredients, but also have a rich aromatic smell. At the same time, they have significant transdermal absorption ability, which can effectively meet the market's consumer demand for healthy and effective cosmetics and increase the value of cosmetic products. Modern research has fully demonstrated the biological activities of dried ginger essential oil, such as antioxidant, anti-aging, antibacterial and anti-inflammatory, and it has extremely high application potential and development and utilization value in the fields of medicine, food, spices and cosmetics.

[0004] However, dried ginger essential oil is a plant essential oil with disadvantages such as poor water solubility, high volatility and poor stability, which limits its wide clinical application.

[0005] It is of great significance to develop a dry ginger essential oil mask with good wettability, high moisturizing rate and safety. Summary of the invention

[0006] The object of the present invention is to provide an electrospinning solution of a dry ginger essential oil nanofiber mask, a nanofiber mask and a preparation method thereof, in view of the fact that the existing technology has the disadvantages of poor water solubility, high volatility and poor stability of dry ginger essential oil, which limits its wide application in beauty and skin care. Polyvinyl alcohol, hyaluronic acid, dry ginger essential oil inclusion compound and water are used as raw materials, and the inclusion rate of the dry ginger essential oil inclusion compound and the ratio between the various raw materials are controlled, so that the nanofiber mask loaded with the dry ginger essential oil inclusion compound prepared by the electrospinning solution has a smooth surface, a compact structure, good hydrophilicity and wetting properties, high safety and moisture retention, and is easy to promote and apply.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is:

[0008] An electrospinning solution for a dried ginger essential oil nanofiber facial mask is prepared by including the following raw materials in parts by weight:

[0009] 1.5-2 parts of polyvinyl alcohol; 0.5-1 part of hyaluronic acid; 0.4-1 part of dried ginger essential oil inclusion compound; 18-22 parts of water; wherein the inclusion rate of the dried ginger essential oil inclusion compound is above 80%.

[0010] The electrospinning solution of the dried ginger essential oil nanofiber mask provided in the present application uses polyvinyl alcohol, hyaluronic acid, dried ginger essential oil inclusion compound and water as raw materials, and controls the inclusion rate of the dried ginger essential oil inclusion compound and the ratio between the various raw materials, so that the nanofiber mask loaded with the dried ginger essential oil inclusion compound prepared by using the electrospinning solution has a smooth surface, a compact structure, good hydrophilicity and wetting properties, high safety and moisturizing properties, and is easy to promote and apply.

[0011] Research has found that the dried ginger essential oil inclusion complex is an inclusion complex formed by the dried ginger essential oil as the active substance encapsulated in the pores of cyclodextrin.

[0012] Furthermore, the inclusion rate of dried ginger essential oil needs to reach more than 80%, which can not only make the inclusion compound achieve good resource utilization, but on the other hand, the study found that the inclusion rate of dried ginger essential oil inclusion compound is too low, the state of the formed inclusion compound is not good, and the facial mask made later will have poor shape, and the moisturizing rate and wetting rate will be adversely affected.

[0013] Furthermore, the polyvinyl alcohol is polyvinyl alcohol 1788.

[0014] Furthermore, the added mass ratio of the dried ginger essential oil inclusion compound and polyvinyl alcohol is 0.25 to 0.5: 1. The study found that the added mass of the dried ginger essential oil inclusion compound and polyvinyl alcohol is a key factor affecting the wettability and moisturizing rate of the dried ginger essential oil nanofiber mask; preferably, the added mass ratio of the dried ginger essential oil inclusion compound and polyvinyl alcohol is 0.4 to 0.5: 1.

[0015] Furthermore, the inclusion rate of the dried ginger essential oil inclusion compound is above 83%. Through experiments, it is found that the inclusion rate of the dried ginger essential oil inclusion compound directly affects the morphology of the dried ginger essential oil inclusion compound in the nanofiber mask and the quality of the nanofiber mask. Controlling the inclusion rate of the dried ginger essential oil inclusion compound to be above 80% can ensure the high quality of the nanofiber mask and ensure good wettability and moisturizing properties. More preferably, the inclusion rate of the dried ginger essential oil inclusion compound is above 85%.

[0016] Furthermore, the dried ginger essential oil inclusion compound is prepared by the following method:

[0017] Step 1, slowly dripping the ethanol solution of dried ginger essential oil into the cyclodextrin aqueous solution for reaction, mixing evenly, cooling to room temperature, and refrigerating for standby use; wherein the mass ratio of dried ginger essential oil to cyclodextrin is 1:3.5-4.5; the reaction temperature is 35°C-45°C, and the reaction time is 50-60min;

[0018] Step 2: centrifuge the material of step 1, and dry and grind the centrifugal precipitate to obtain the dried ginger essential oil inclusion compound.

[0019] The present application provides a method for preparing a dried ginger essential oil inclusion compound. First, a dried ginger essential oil ethanol solution is slowly dripped into a cyclodextrin aqueous solution for reaction, mixed evenly, cooled to room temperature, and refrigerated for standby use; then, the material is centrifuged, and the centrifugal precipitate is dried and ground to obtain a dried ginger essential oil inclusion compound. By controlling the added mass ratio of dried ginger essential oil and β-cyclodextrin, the reaction temperature and the reaction time, the inclusion rate of the dried ginger essential oil inclusion compound can reach more than 80%, meeting the performance requirements of the subsequent nanofiber mask.

[0020] The cyclodextrin inclusion delivery system is an active substance processing technology. The cyclodextrin inclusion complex, also known as a "molecular capsule", contains non-polar pores and a hydrophilic surface. The active substance can be encapsulated in the pores of the cyclodextrin to form an inclusion complex, thereby isolating the active substance from the surrounding environment and enhancing the stability of the active substance. At the same time, it can also prevent the active substance from encountering oxygen, light, heat or other compounds that may cause its properties to become unstable, and can also conceal the unpleasant odor of the encapsulated active substance.

[0021] Preferably, the cyclodextrin is β-cyclodextrin.

[0022] Furthermore, the mass ratio of dried ginger essential oil to cyclodextrin is 1:4-4.5.

[0023] Furthermore, in step 1, the reaction temperature is 40°C to 45°C.

[0024] Furthermore, in step 1, the reaction time is 55 to 60 minutes.

[0025] Appropriate reaction temperature, reaction time and control of the mass ratio of dried ginger essential oil to β-cyclodextrin can effectively increase the inclusion rate of dried ginger essential oil.

[0026] Another object of the present invention is to provide a method for preparing the electrospinning solution.

[0027] The preparation method of the electrospinning solution of the dried ginger essential oil nanofiber mask comprises the following steps:

[0028] S1, adding polyvinyl alcohol into water and heating to dissolve;

[0029] S2, adding hyaluronic acid to the material in S1, dissolving it, and performing the first stirring;

[0030] S3, adding the dried ginger essential oil inclusion compound to the solution of S2, and stirring for the second time;

[0031] S4, subjecting the solution stirred in S3 to ultrasonic defoaming to obtain an electrospinning solution.

[0032] The present application provides a method for preparing an electrospinning solution of a dried ginger essential oil nanofiber mask, comprising the following steps: S1, adding polyvinyl alcohol to water and heating to dissolve; S2, adding hyaluronic acid to the material of S1, dissolving, and performing a first stirring; S3, adding a dried ginger essential oil inclusion compound to the solution of S2, and performing a second stirring; S4, ultrasonically defoaming the solution after stirring in S3 to obtain an electrospinning solution. The preparation method is simple to operate and easy to control.

[0033] Furthermore, in S2, the first stirring time is 4 h to 6 h.

[0034] Furthermore, in S3, the second stirring time is 1 h to 3 h.

[0035] A dried ginger essential oil nanofiber facial mask is prepared by adopting the electrostatic spinning solution of the dried ginger essential oil nanofiber facial mask.

[0036] A method for preparing the above-mentioned dried ginger essential oil nanofiber mask is to add the electrospinning solution into the electrospinning equipment, with a liquid feeding rate of 0.3-0.5 mL / h and a roller speed of 250-350 r / min. A suitable electrospinning process can ensure better formability of the nanofiber mask.

[0037] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0038] 1. The electrospinning solution of the dried ginger essential oil nanofiber mask provided in the present application uses polyvinyl alcohol, hyaluronic acid, dried ginger essential oil inclusion compound and water as raw materials, and controls the inclusion rate of the dried ginger essential oil inclusion compound and the ratio between the various raw materials, so that the nanofiber mask loaded with the dried ginger essential oil inclusion compound prepared by using the electrospinning solution has a smooth surface, a compact structure, good hydrophilicity and wetting properties, a moisturizing rate of more than 45%, high safety and moisturizing properties, and is easy to promote and apply.

[0039] 2. The present application provides a method for preparing a dried ginger essential oil inclusion compound. First, a dried ginger essential oil ethanol solution is slowly dripped into a cyclodextrin aqueous solution for reaction, mixed evenly, cooled to room temperature, and refrigerated for standby use; then, the material is centrifuged, and the centrifugal precipitate is dried and ground to obtain a dried ginger essential oil inclusion compound. By controlling the added mass ratio of dried ginger essential oil and cyclodextrin, the reaction temperature and the reaction time, the inclusion rate of the dried ginger essential oil inclusion compound can reach more than 80%, meeting the performance requirements of the subsequent nanofiber mask.

[0040] 3. The present application provides a method for preparing an electrospinning solution of a dried ginger essential oil nanofiber mask, comprising the following steps: S1, adding polyvinyl alcohol to water and heating to dissolve; S2, adding hyaluronic acid to the material in S1, dissolving it, and performing a first stirring; S3, adding the dried ginger essential oil inclusion compound to the solution in S2, and performing a second stirring; S4, ultrasonically defoaming the solution after stirring in S3 to obtain an electrospinning solution. The preparation method is simple to operate and easy to control. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 This is the diameter diagram of the inhibition zone of dried ginger essential oil against two bacteria; Figure 1 (A) Staphylococcus aureus; Figure 1 (B) Propionibacterium acnes.

[0042] Figure 2 This is the MIC determination diagram of dried ginger essential oil against two bacteria; Figure 2 (A) Staphylococcus aureus; Figure 2 (B) Propionibacterium acnes.

[0043] Figure 3 This is the determination diagram of the MBC of two bacteria by dried ginger essential oil; Figure 3 (A) Staphylococcus aureus; Figure 3 (B) Propionibacterium acnes.

[0044] Figure 4 This graph shows the effect of dried ginger essential oil on the general condition of the skin in mice with skin aging model.

[0045] Figure 5 This is a test chart of the effect of dried ginger essential oil on the epidermal thickness of skin aging mice; Figure 5 (A) HE staining of mouse skin tissue (200×); Figure 5 (B) Epidermal thickness analysis (n=5), compared with the normal group, ##P<0.01; compared with the model group, *P<0.05, **P<0.01.

[0046] Figure 6This is the effect of dried ginger essential oil on the expression of TNF-α and MMP-1 in the skin of skin aging mice (n=6); compared with the normal group, #P<0.05, ##P<0.01; compared with the model group, **P<0.01.

[0047] Figure 7 SEM images of β-cyclodextrin (a), physical mixture, dried ginger essential oil (b) and β-cyclodextrin inclusion complex (c).

[0048] Figure 8 FTIR images of β-cyclodextrin (a), dried ginger essential oil (b), physical mixture (c) and dried ginger essential oil-β-cyclodextrin (d).

[0049] Fig. 9 XRD patterns of β-cyclodextrin (A), physical mixture (B) and dried ginger essential oil β-cyclodextrin inclusion complex (C).

[0050] Fig.10 TGA diagrams of β-cyclodextrin, physical mixture and dried ginger essential oil β-cyclodextrin inclusion complex.

[0051] Fig.11 Flow chart for preparing spinning solution.

[0052] Fig.12 (a-ff) SEM images of nanofiber masks; (a′-f′) fiber diameter distribution of each sample.

[0053] Fig.13 This is the infrared spectrum of the nanofiber mask.

[0054] Fig.14 This is the static water contact angle test data of the nanofiber mask.

[0055] Fig.15 This is the test data of red blood cell hemolysis rate of nanofiber mask.

[0056] Fig.16 The chicken embryo chorioallantoic membrane test for the nanofiber mask. DETAILED DESCRIPTION

[0057] The present invention will be described in detail below in conjunction with the accompanying drawings.

[0058] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0059] The following embodiment is a process for extracting dried ginger essential oil: taking dried ginger coarse powder, adding 10 times the amount of extraction solvent and 1% cellulase, adjusting the pH value to 5, performing enzymatic hydrolysis at 47° C. for 1 hour, and performing steam distillation extraction for 3 hours to obtain dried ginger essential oil.

[0060] Example 1

[0061] Evaluation of the anti-acne and antibacterial effects of dried ginger essential oil

[0062] (1) Antibacterial activity study

[0063] Dilute the Staphylococcus aureus liquid with sterile PBS solution to 106CFU / mL, and then draw 100μL and evenly spread it on the LB solid culture medium. Take 10μL of the sterilized sample and drop it on the filter paper. After the sample is completely absorbed, place the filter paper on the surface of the culture medium so that the sample and the culture medium are fully in contact, and place it in a 37℃ constant temperature incubator for 24h. After the culture is completed, take it out and take a picture with an ordinary camera and use the cross method to determine the size of the inhibition zone. The test is repeated three times (the culture conditions of Propionibacterium acnes are the same as above).

[0064] (2) Minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) test

[0065] Prepare LB liquid culture medium containing 0.125 to 8 mg / mL of essential oil at a final concentration and place it in a test tube, and take 100 μL of bacterial suspension and add it. Place the test tube in a shaker at 37°C and 180 r / min for 24 hours, and observe bacterial growth. The essential oil concentration corresponding to the group without obvious turbidity is the MIC value; then, in all groups without obvious turbidity, take 50 μL of each bacterial suspension and spread it on the surface of the LB culture medium, incubate for 24 hours under the same temperature conditions, and the essential oil concentration corresponding to the group without bacterial growth is the MBC value. The experiment is repeated three times.

[0066] The results showed that the quantitative analysis of the inhibition zone diameter, MIC, and MBC of dried ginger essential oil (GEO) on the two tested strains is shown in Table 1. The results showed that dried ginger essential oil showed different MIC and MBC value ranges for the two tested strains, among which Propionibacterium acnes showed higher sensitivity to dried ginger essential oil than Staphylococcus aureus, with MIC and MBC values ​​of 2 mg / mL and 4 mg / mL, respectively, and Staphylococcus aureus MIC and MBC values ​​of 4 mg / mL and 8 mg / mL, respectively, which is consistent with the above test results of determining the inhibition zone diameter of the two bacteria ( Figure 1-3 ).

[0067] Table 1 Determination results of inhibition zone, minimum inhibitory concentration and minimum bactericidal concentration of dried ginger essential oil on the tested strains

[0068] Bacterial species DIZ(mm) MIC (mg / mL) MBC (mg / mL) Staphylococcus aureus 2 4 8 Propionibacterium acnes 6 2 4

[0069] Effect of dried ginger essential oil on delaying skin aging in mice

[0070] Twenty-four healthy female Kunming mice (18-22 g) were housed in a standard animal laboratory (25°C, 12 h light-dark alternation) for one week and allowed free access to food and water. The animal experiment was approved by the Ethics Committee of the School of Pharmacy of Chengdu University of Traditional Chinese Medicine. An appropriate amount of dried ginger essential oil was dissolved in ethanol propylene glycol solvent (3:7, v / v) to prepare 4 mg / mL and 8 mg / mL solutions respectively.

[0071] (1) Skin aging mouse model and drug administration

[0072] Skin aging mice were mainly induced by subcutaneous injection of 10% D-galactose combined with ultraviolet light irradiation for 42 days. Twenty-four female KM mice were randomly divided into 4 groups (n=6): normal group (NC), model group (MC), low-dose group (GEO-L) and high-dose group (GEO-H), with 6 mice in each group. All groups were depilated. Except for the normal group, the other three groups were subcutaneously injected with 10% D-galactose (10μL / g) on ​​the back of the neck every day. After the injection, UV irradiation was performed. The UV irradiation time was 40min / d. The light source was about 40cm vertically away from the mouse. It was irradiated every other day for 42 days. Half an hour before modeling every day, 100μL of ethanol propylene glycol solvent was administered to the skin of the model group; 100μL of 4mg / mL dried ginger essential oil solution was applied to the GEO-L group; and 100μL of 8mg / mL dried ginger essential oil solution was applied to the GEO-H group.

[0073] During the experiment, mice were free to eat and drink, and the drinking water was changed every day. If acute inflammation such as skin blisters, erosion, and exudation appeared during ultraviolet irradiation, irradiation should be suspended for 2 to 3 days and then continued after the symptoms improved.

[0074] Effects of dried ginger essential oil on the general condition of the skin in mice with skin aging model Figure 4 As shown. The skin of mice in the normal group was smooth and elastic, without erythema or wrinkles. 42 days after modeling, compared with the normal group, the skin of the model group was rough, erythema appeared, dull and dull, with deep and coarse wrinkles, and the epidermis had an orange peel or leather-like appearance and poor elasticity. Compared with the model group, the skin condition of mice improved to varying degrees after intervention with dried ginger essential oil. Erythema and a small number of fine wrinkles appeared in the GEO-L group, and the skin of the GEO-H group was significantly smoother and had fewer wrinkles.

[0075] (2) Histopathological analysis

[0076] After 42 days of continuous modeling, the mice were fasted for 24 hours and killed by cervical dislocation. Tissues of approximately 0.5 cm × 0.5 cm were taken and fixed by immersion in 4% paraformaldehyde solution. The fixed skin tissues were taken out for paraffin embedding, sectioning, dewaxing, dehydration, and made into 4 mm thick sections. HE staining was used to observe the dermis thickness in the skin tissue.

[0077] Effect of dried ginger essential oil on epidermal thickness in skin aging mice Figure 5 The results showed that the epidermis of the normal group mice was thin and structurally intact; compared with the normal group, the epidermis of the model group mice was significantly thickened (P<0.01); compared with the model group, both GEO-L and GEO-H groups could significantly reduce the epidermis thickness of the skin aging model mice (P<0.05, P<0.01). This shows that dried ginger essential oil can improve the epidermis thickening phenomenon caused by skin aging in mice.

[0078] (3) Biochemical index detection

[0079] An appropriate amount of mouse skin was taken to prepare tissue homogenate, and the TNF-α and MMP-1 proteins were quantified using a BCA protein concentration assay kit, and then the TNF-α and MMP-1 contents were detected according to the instructions of the ELISA kit.

[0080] The results of TNF-α and MMP-1 content determination were as follows Figure 6 As shown. Compared with the normal group, the protein levels of TNFα and MMP-1 in the model group were significantly increased (P<0.01, P<0.05). Compared with the model group, both GEO-L and GEO-H groups could significantly improve the trend of increased TNF-α and MMP-1 levels in the skin aging mouse model (P<0.01). The results showed that dried ginger essential oil can reduce the inflammatory response of skin aging model mice by downregulating the expression level of TNF-α protein, while reducing the production of MMP-1, thereby delaying the skin aging of mice.

[0081] Example 2

[0082] Example 2-1

[0083] Preparation of β-cyclodextrin inclusion complex of dried ginger essential oil

[0084] Take β-cyclodextrin, add it into pure water, heat and stir until it is completely dissolved, and set aside;

[0085] Take dried ginger essential oil and mix it with 10 times the mass of anhydrous ethanol for later use;

[0086] Step 1, slowly dripping the ethanol solution of dried ginger essential oil into the β-cyclodextrin aqueous solution for reaction, mixing evenly, cooling to room temperature, and refrigerating for standby use; wherein the mass ratio of dried ginger essential oil to β-cyclodextrin is 1:4; the reaction temperature is 40° C., and the reaction time is 60 min;

[0087] Step 2: centrifuge the material of step 1, and dry and grind the centrifugal precipitate to obtain the dried ginger essential oil inclusion compound.

[0088] Example 2-2

[0089] Preparation of β-cyclodextrin inclusion complex of dried ginger essential oil

[0090] Take β-cyclodextrin, add it into pure water, heat and stir until it is completely dissolved, and set aside;

[0091] Take dried ginger essential oil and mix it with 10 times the mass of anhydrous ethanol for later use;

[0092] The dried ginger essential oil ethanol solution is slowly dripped into the β-cyclodextrin aqueous solution for reaction, wherein the mass ratio of the dried ginger essential oil to the β-cyclodextrin is 1:3.5; the reaction temperature is 45°C, and the reaction time is 60min; the mixture is evenly mixed, cooled to room temperature, refrigerated overnight at 4°C, centrifuged (8000rpm, 10min, 4°C), and the centrifugal precipitate is dried and ground to obtain the dried ginger essential oil inclusion compound.

[0093] Example 2-3

[0094] Preparation of β-cyclodextrin inclusion complex of dried ginger essential oil

[0095] Take β-cyclodextrin, add it into pure water, heat and stir until it is completely dissolved, and set aside;

[0096] Take dried ginger essential oil and mix it with 10 times the mass of anhydrous ethanol for later use;

[0097] The dried ginger essential oil ethanol solution is slowly dripped into the β-cyclodextrin aqueous solution for reaction, wherein the mass ratio of the dried ginger essential oil to the β-cyclodextrin is 1:4.5; the reaction temperature is 35°C, and the reaction time is 50 min; the mixture is evenly mixed, cooled to room temperature, refrigerated overnight at 4°C, centrifuged (8000 rpm, 10 min, 4°C), and the centrifugal precipitate is dried and ground to obtain a dried ginger essential oil inclusion compound.

[0098] Comparative Example 2-1

[0099] Compared with Example 2-1, in Comparative Example 2-1, when preparing the dried ginger essential oil β-cyclodextrin inclusion complex, the mass ratio of dried ginger essential oil and β-cyclodextrin was changed, the sum of the masses of dried ginger essential oil and β-cyclodextrin remained unchanged, and the other process parameters were the same as those in Example 2-1.

[0100] Preparation of β-cyclodextrin inclusion complex of dried ginger essential oil

[0101] Take β-cyclodextrin, add it into pure water, heat and stir until it is completely dissolved, and set aside;

[0102] Take dried ginger essential oil and mix it with 10 times the mass of anhydrous ethanol for later use;

[0103] Step 1, slowly dripping the dried ginger essential oil ethanol solution into the β-cyclodextrin aqueous solution for reaction, mixing evenly, cooling to room temperature, and refrigerating for standby use; wherein the mass ratio of the dried ginger essential oil to the β-cyclodextrin is 1:2.5; the reaction temperature is 40° C., and the reaction time is 60 min;

[0104] Step 2: centrifuge the material of step 1, and dry and grind the centrifugal precipitate to obtain the dried ginger essential oil inclusion compound.

[0105] Comparative Example 2-2

[0106] Compared with Example 2-1, in Comparative Example 2-2, when preparing the dried ginger essential oil β-cyclodextrin inclusion complex, the mass ratio of dried ginger essential oil and β-cyclodextrin was changed, the sum of the masses of dried ginger essential oil and β-cyclodextrin remained unchanged, and the other process parameters were the same as those in Example 2-1.

[0107] Preparation of β-cyclodextrin inclusion complex of dried ginger essential oil

[0108] Take β-cyclodextrin, add it into pure water, heat and stir until it is completely dissolved, and set aside;

[0109] Take dried ginger essential oil and mix it with 10 times the mass of anhydrous ethanol for later use;

[0110] Step 1, slowly dripping the ethanol solution of dried ginger essential oil into the β-cyclodextrin aqueous solution for reaction, mixing evenly, cooling to room temperature, and refrigerating for standby use; wherein the mass ratio of dried ginger essential oil to β-cyclodextrin is 1:6; the reaction temperature is 40° C., and the reaction time is 60 min;

[0111] Step 2: centrifuge the material of step 1, and dry and grind the centrifugal precipitate to obtain the dried ginger essential oil inclusion compound.

[0112] Comparative Examples 2-3

[0113] Compared with Example 2-1, in Comparative Example 2-3, the reaction temperature in step 1 was changed when preparing the dried ginger essential oil β-cyclodextrin inclusion complex, and the other process parameters were the same as those of Example 2-1.

[0114] Preparation of β-cyclodextrin inclusion complex of dried ginger essential oil

[0115] Take β-cyclodextrin, add it into pure water, heat and stir until it is completely dissolved, and set aside;

[0116] Take dried ginger essential oil and mix it with 10 times the mass of anhydrous ethanol for later use;

[0117] Step 1, slowly dripping the ethanol solution of dried ginger essential oil into the β-cyclodextrin aqueous solution for reaction, mixing evenly, cooling to room temperature, and refrigerating for standby use; wherein the mass ratio of dried ginger essential oil to β-cyclodextrin is 1:4; the reaction temperature is 25°C, and the reaction time is 60min;

[0118] Step 2: centrifuge the material of step 1, and dry and grind the centrifugal precipitate to obtain the dried ginger essential oil inclusion compound.

[0119] Comparative Examples 2-4

[0120] Compared with Example 2-1, in Comparative Example 2-4, the reaction temperature in step 1 was changed when preparing the dried ginger essential oil β-cyclodextrin inclusion complex, and the other process parameters were the same as those of Example 2-1.

[0121] Preparation of β-cyclodextrin inclusion complex of dried ginger essential oil

[0122] Take β-cyclodextrin, add it into pure water, heat and stir until it is completely dissolved, and set aside;

[0123] Take dried ginger essential oil and mix it with 10 times the mass of anhydrous ethanol for later use;

[0124] Step 1, slowly dripping the ethanol solution of dried ginger essential oil into the β-cyclodextrin aqueous solution for reaction, mixing evenly, cooling to room temperature, and refrigerating for standby use; wherein the mass ratio of dried ginger essential oil to β-cyclodextrin is 1:4; the reaction temperature is 80° C., and the reaction time is 60 min;

[0125] Step 2: centrifuge the material of step 1, and dry and grind the centrifugal precipitate to obtain the dried ginger essential oil inclusion compound.

[0126] Comparative Examples 2-5

[0127] Compared with Example 2-1, in Comparative Example 2-5, the reaction time in step 1 was changed when preparing the dried ginger essential oil β-cyclodextrin inclusion complex, and the other process parameters were the same as those of Example 2-1.

[0128] Preparation of β-cyclodextrin inclusion complex of dried ginger essential oil

[0129] Take β-cyclodextrin, add it into pure water, heat and stir until it is completely dissolved, and set aside;

[0130] Take dried ginger essential oil and mix it with 10 times the mass of anhydrous ethanol for later use;

[0131] Step 1, slowly dripping the ethanol solution of dried ginger essential oil into the β-cyclodextrin aqueous solution for reaction, mixing evenly, cooling to room temperature, and refrigerating for standby use; wherein the mass ratio of dried ginger essential oil to β-cyclodextrin is 1:4; the reaction temperature is 40° C., and the reaction time is 40 min;

[0132] Step 2: centrifuge the material of step 1, and dry and grind the centrifugal precipitate to obtain the dried ginger essential oil inclusion compound.

[0133] Comparative Examples 2-6

[0134] Compared with Example 2-1, in Comparative Example 2-6, the reaction temperature in step 1 was changed when preparing the dried ginger essential oil β-cyclodextrin inclusion complex, and the other process parameters were the same as those of Example 2-1.

[0135] Preparation of β-cyclodextrin inclusion complex of dried ginger essential oil

[0136] Take β-cyclodextrin, add it into pure water, heat and stir until it is completely dissolved, and set aside;

[0137] Take dried ginger essential oil and mix it with 10 times the mass of anhydrous ethanol for later use;

[0138] Step 1, slowly dripping the ethanol solution of dried ginger essential oil into the β-cyclodextrin aqueous solution for reaction, mixing evenly, cooling to room temperature, and refrigerating for standby use; wherein the mass ratio of dried ginger essential oil to β-cyclodextrin is 1:4; the reaction temperature is 40° C., and the reaction time is 80 min;

[0139] Step 2: centrifuge the material of step 1, and dry and grind the centrifugal precipitate to obtain the dried ginger essential oil inclusion compound.

[0140] test

[0141] Reference, comprehensive score is calculated by weighting coefficient of inclusion rate 0.7 and weighting coefficient of yield 0.3. The detailed formula is as follows:

[0142]

[0143]

[0144] Wherein: m represents the amount of included dried ginger essential oil; M represents the amount of added dried ginger essential oil.

[0145] The inclusion compound yield was calculated according to formula (1-1). An appropriate amount of inclusion compound was weighed and mixed with anhydrous ethanol, ultrasonicated for 1 hour, and then centrifuged. The upper clear liquid was taken to measure its absorbance value, and the inclusion rate was calculated according to formula (1-2); the specific test results are shown in Table 2.

[0146] Table 2

[0147] / Inclusion rate (%) Inclusion compound yield (%) Example 2-1 85.30 84.11 Example 2-2 83.56 83.41 Example 2-3 81.18 80.94 Comparative Example 2-1 64.67 72.14 Comparative Example 2-2 73.15 42.66 Comparative Examples 2-3 66.32 53.87 Comparative Examples 2-4 62.38 67.99 Comparative Examples 2-5 70.25 68.56 Comparative Examples 2-6 65.88 75.16

[0148] Study on the physical and chemical properties of GEO / βCD-IC (β-cyclodextrin inclusion complex of dried ginger essential oil)

[0149] (1) Scanning electron microscopy (SEM)

[0150] Take appropriate amounts of β-CD (β-cyclodextrin), physical mixture (mixture of dried ginger essential oil and β-cyclodextrin) and GEO / βCD-IC prepared in Example 2-1, and make them conductive adhesive, spray gold and then observe them by SEM. Compare the differences in the scanned images of the three samples and analyze the morphological changes before and after the β-CD forms the inclusion complex. The results are as follows Figure 7 As shown in a, β-CD is an irregular block with large particles, a flat surface, a compact structure, and strong integrity. Figure 7 As shown in b, GEO in the physical mixture is adsorbed on the β-CD surface in the form of milky white opaque substance. Figure 7 c It can be seen that the particles of GEO / βCD-ID are smaller, tend to be uniform in size, and have strong aggregation. The surface morphology of GEO / βCD-ID is obviously different from that of the physical mixture, suggesting that β-CD and GEO combine to form a new complex.

[0151] (2) Fourier transform infrared spectroscopy (FTIR)

[0152] FTIR was used to analyze GEO, β-CD, physical mixture and GEO / βCD-IC. The scanning wave number range was 400-4000cm-1, the resolution was 4cm-1, and the number of scans was 32. The FTIR results are shown in Figure 8 shown. Figure 8 a is the FTIR graph of β-CD; its characteristic peaks are 3385.04cm-1, 2926.07cm-1, 1157.31cm-1, 1028.83cm-1 and 1652.62cm-1, representing the stretching vibrations of OH, -CH3, CO, COC and the bending vibrations of HOH in β-CD, respectively. Figure 8 b is the FTIR spectrum of dried ginger essential oil, which has characteristic absorption peaks at 2960.78 cm-1 (-CH3), 2919.41 cm-1 and 2858.07 cm-1 (-CH2). Figure 8 c is the FTIR graph of the physical mixture of GEO and β-CD, which has characteristic absorption peaks at 3382.80cm-1(-OH), 2926.73cm-1(-CH3) and 1654.56cm-1(HOH), which are almost completely consistent with the infrared absorption spectrum of β-CD; it has common absorption peaks of GEO and β-CD, and the absorption peak of GEO at 1376.92cm-1 is transformed to 1369.64cm-1. Figure 8d is the FTIR graph of GEO / βCD-IC. The peaks of GEO at 2858.07cm-1, 2960.78cm-1, and 1446.60cm-1 disappeared, indicating that GEO and β-CD had a strong physical cross-linking effect. It can be inferred that the dried ginger essential oil and cyclodextrin formed an inclusion complex, and the inclusion complex was successfully prepared.

[0153] (3) X-ray diffraction analysis (XRD)

[0154] The physicochemical properties of β-CD, physical mixture and GEO / βCD-IC were analyzed and recorded in the range of 3-60°. The Cu / Kα radiation conditions were 45 kV, 30 mA, and the scanning rate was 5° min-1. The diffraction patterns were obtained and analyzed. Fig. 9 As shown in A, the diffraction peaks of β-CD are 6.22, 8.96, 10.60, 12.38, 19.40, 22.74, 27.06, 31.72, 34.92, etc.; it is in a crystalline state. Fig. 9 As shown in Figure B, there is almost no significant difference between the X-ray diffraction patterns of the physical mixture and β-CD, indicating that no new phase is generated. Fig. 9 As shown in Figure C, the diffraction peaks of GEO / βCD-ID are 7.12, 9.80, 11.82, 15.30, 17.54, 18.70, 23.74 and 25.90, etc. By comparison, it can be seen that the X-ray diffraction spectrum of GEO / βCD-ID is significantly different from that of β-CD and physical mixtures. GEO exists in the form of guest molecules in β-CD, and the formed crystals are significantly different from the β-CD crystal form, accompanied by changes in molecular structure. At the same time, after GEO and β-CD are combined, most of the diffraction peaks of β-CD crystals disappear, which indicates that the addition of dried ginger essential oil causes the molecular structure of β-CD to rearrange.

[0155] (4) Thermogravimetric analysis (TGA)

[0156] TGA was used to analyze β-CD, physical mixture and optimized GEO / βCD-IC. 5 mg of sample was placed in the crucible of the thermogravimetric analyzer. 99.99% nitrogen was used as the dynamic gas with a flow rate of 100 mL·h-1. The heating rate was 20℃·min-1 and the temperature range was between 30 and 500℃. The results are shown in Figure 2. Fig.10As shown in the figure, β-CD underwent two obvious thermal degradations, one of which occurred at 64.30-134.72℃, mainly due to water evaporation; the other occurred between 288.88 and 402.70℃, mainly due to the degradation of β-CD molecules. However, the physical mixture and GEO / βCD-IC only had one significant degradation process. Before the thermal degradation of β-CD, the two always showed a slow and stable degradation state. Throughout the thermal degradation process, the water loss rate of GEO / βCD-IC was always lower than that of the physical mixture, indicating that GEO / βCD-IC has better thermal stability.

[0157] Example 3

[0158] Preparation of nanofiber facial mask loaded with dried ginger essential oil-cyclodextrin inclusion complex

[0159] (1) Preparation of spinning solution

[0160] Dissolve polyvinyl alcohol 1788 (PVA) in pure water and heat and stir until completely dissolved to obtain an 8% (w / v) PVA solution. Dissolve a certain amount of (hyaluronic acid) HA in the above PVA solution, and stir the PVA-HA solution at room temperature for 5 hours. Then, dry ginger essential oil at a concentration of 2 mg / mL and a cyclodextrin inclusion complex containing dry ginger essential oil (prepared in Example 2-1) at concentrations of 2, 3 and 4 mg / mL are dissolved in the PVA-HA solution and stirred for 2 hours. Finally, the above solution is ultrasonically defoamed for 15 minutes to obtain uniform PVA, PVA-HA, PVA-HA-GEO, PVA-HA-GEO / βCD-2, PVAHA-GEO / βCD-3, PVA-HA-GEO / βCD-4 electrospinning solutions. The specific configuration process is as follows Fig.11 As shown, the ratio is shown in Table 3.

[0161] Table 3 Proportion of spinning solution

[0162]

[0163] (2) Electrospinning parameter setting

[0164] In this experiment, an electrospinning device was used to prepare a nanofiber mask loaded with dried ginger essential oil-cyclodextrin inclusion complex. The relevant spinning parameters are shown in Table 4.

[0165] Table 4 Spinning related parameters

[0166]

[0167]

[0168] Performance testing and characterization of nanofiber facial mask loaded with dried ginger essential oil-cyclodextrin inclusion complex

[0169] (1) Microstructure characterization

[0170] Each group of nanofiber masks was cut into samples of a certain size, sprayed with an ion sputtering device, and scanned and photographed with a SEM at a magnification of 20,000 times. Image J was used to measure each sample 50 times to determine the average nanofiber diameter of each sample, and Origin software was used to analyze the diameter distribution of the nanofibers and calculate the average diameter.

[0171] SEM images are shown in Fig.12 As shown, the results show that the nanofiber mask is composed of a large number of randomly oriented nanofibers forming a three-dimensional network structure, with diameters of 155.76±22.96nm, 109.94±17.57nm, 69.86±19.99nm, 92.16±23.26nm, 107.02±18.04nm and 94.22±21.77nm, respectively. The nanofibers obtained by electrospinning pure PVA and PVA\HA solutions are uniformly distributed and have no beads. After adding GEO, GEO is not effectively encapsulated, the nanofiber properties are unstable, and a large number of spindles appear. GEO added in the form of inclusion complex is effectively encapsulated in the nanofibers, and the nanofibers are uniform and have no beads. The slight change in fiber diameter may be related to the different viscosity and conductivity of the spinning solution.

[0172] (2) Chemical structure analysis

[0173] The FTIR measurements of PVA, PVA-HA, PVA-HA-GEO and PVA-HA-GEO / βCD nanofiber masks were performed using an infrared spectrometer in the wavelength range of 4000-600 cm-1.

[0174] FTIR analysis of nanofiber mask Fig.13 As shown in the figure, the broad and deep absorption peak at 3305cm-1 is attributed to the superimposed characteristic absorption peak of the stretching vibration of the OH bond or NH bond. The peak at 2931cm-1 indicates the stretching vibration of the CH bond of the alkyl group, and the absorption peak at 1249cm-1 is mainly due to the CH angle vibration of the peptide bond. Fig.13 It can be seen that the infrared spectra of PVA, PVA-HA, PVA-HA-GEO, PVA-HA-GEO / βCD-2, PVA-HAGEO / βCD-3, and PVA-HA-GEO / βCD-4 nanofiber masks are similar (displacement change is ±5 cm-1), indicating physical mixing without chemical reaction, which suggests that GEO is constrained in the fiber dressing by van der Waals forces.

[0175] (3) Contact angle test

[0176] The contact angle was used to characterize the hydrophilicity of the nanofiber mask. The prepared nanofiber mask was made into a 1 cm × 3 cm strip sample, and the contact angle between the mask and the water drop was observed using the sessile drop method.

[0177] like Fig.14 As shown in the figure, the average contact angles of PVA, PVA-HA, PVA-HA-GEO, PVA-HAGEO / βCD-2, PVA-HA-GEO / βCD-3, and PVA-HA-GEO / βCD-4 nanofiber masks at 150ms were 59.52°, 50.79°, 53.23°, 44.74°, 56.90°, and 61.67°. The results show that the nanofiber mask is hydrophilic, and the addition of a large number of polar groups in HA reduces the surface static contact angle and increases the hydrophilicity of the nanofiber mask. With the increase in the concentration of the lipophilic component GEO, the hydrophilicity of the nanofiber mask is affected to a certain extent. Overall, the PVA-HA-GEO / βCD nanofiber mask has good wettability.

[0178] (4) Moisturizing efficacy test

[0179] A 3cm×3cm test area was marked on the inside of the subject's arm, with each test area spaced no less than 1cm apart. A skin tester was used to measure the skin moisture content before applying the nanofiber mask. A proper amount of pure water was evenly sprayed using a spray bottle. A 3cm×3cm nanofiber mask was then applied to the test area. The skin moisture content was measured after the sample test area had been stabilized for 20 minutes. Each group of samples was tested 10 times.

[0180] The results of skin moisture content are shown in Table 5. The average moisture content of the skin tested before the experiment was about 24%. The use of PVA nanofiber mask did not significantly improve the moisture content of the skin. Since HA is a highly hydrophilic substance, the composite effect with PVA is enhanced, which improves the tightness of the nanofiber mask structure, effectively inhibits the diffusion of water molecules, and reduces the water vapor permeability. Therefore, after adding HA, the moisture content on the skin surface has increased to a certain extent, and the average moisture content is about 44%. The average moisture content of PVAHA-GEO nanofiber mask is about 35%, and the moisture content has decreased. The average moisture content of PVA-HAGEO / βCD-2, PVA-HA-GEO / βCD-3, and PVA-HA-GEO / βCD-4 nanofiber masks is about 44%, 46%, and 43%, indicating that the prepared nanofiber mask has good moisturizing ability.

[0181] Table 5 Skin moisture content

[0182]

[0183] (5) Safety evaluation

[0184] ① Red blood cell hemolysis test

[0185] Fresh sterile defibrinated sheep blood was centrifuged to obtain the supernatant, which was diluted with PBS buffer to prepare a red blood cell suspension. The PVA / HA / GEO-βCD-4 nanofiber mask was dissolved in PBS to obtain a 20 mg / mL mask solution, which was then diluted 1.15, 1.25, 1.35 and 1.5 times to obtain samples of different concentrations. The sample solutions of different concentrations were mixed with the red blood cell suspension in a volume ratio of 1:1 (500 μL: 500 μL), and after sufficient reaction by oscillation centrifugation, the absorbance value at 560 nm was determined by an enzyme marker. Each group of samples was tested 3 times. PBS was used as the autohemolysis group, and 100 mg / L SDS solution was used as the full hemolysis group.

[0186] The hemolysis rate HR is calculated as follows:

[0187]

[0188] A1, A2, and A3 are the absorbance values ​​of the test sample group, autohemolysis group, and complete hemolysis group at 560 nm, respectively.

[0189] The PVA-HA-GEO / βCD-4 solution with the highest GEO content was used as the test object for red blood cell hemolysis, and the red blood cell hemolysis rate of each dilution concentration was measured. Fig.15 The results showed that the GEO nanofiber mask with the highest addition amount only caused 4.71% of erythrocyte hemolysis rate, indicating that the toxicity of the nanofiber mask to erythrocytes was negligible.

[0190] ②Chicken embryo chorioallantoic membrane test

[0191] Each group of nanofiber masks was dissolved in PBS to obtain a 10 mg / mL mask solution. 0.3 mL of positive control (1% sodium dodecyl sulfate solution), negative control (0.9% NaCl solution) and mask solution were directly dropped on the surface of the chick embryo chorioallantoic membrane (CAM). After staying for 3 minutes, the CAM surface was gently cleaned with physiological saline and the liquid was poured out. The degree of bleeding, coagulation and vascular hemolysis was immediately observed, and each group was paralleled 6 times. The endpoint scoring method was used, and the stimulation evaluation results were judged according to Table 6 and a score (ES) was given. The average value of the ES score was calculated as follows: ES = (the sum of the degree of bleeding, coagulation and vascular hemolysis observed in 6 chick embryos) / 3.

[0192] Table 6 Evaluation of stimulation results

[0193] End point score Irritation classification ES≤12 No / mild irritation 12<ES<16 Moderate irritation ES≥16 Severe irritation

[0194] The rich vascular network structure of chicken embryo CAM was used to simulate the conjunctival tissue structure. The negative control was 9% normal saline, which had no effect on the CAM vascular network, and the ES value was 0. The positive control used 1% SDS, which had obvious hemolysis and coagulation, and the ES value was 16, indicating that the vascular network was strongly stimulated. The mask liquid made of six nanofiber masks was directly dropped on the CAM surface and tested separately, such as Fig.16 As shown, the evaluation results all showed no hemolysis, indicating that all six nanofiber membranes had no eye irritation.

[0195] Example 3-1

[0196] 1.5 parts of polyvinyl alcohol; 1 part of hyaluronic acid; 0.4 parts of dried ginger essential oil inclusion compound; 22 parts of water;

[0197] Among them, the dried ginger essential oil inclusion compound adopts the product prepared in Example 2-2.

[0198] S1, adding polyvinyl alcohol into water and heating to dissolve;

[0199] S2, adding hyaluronic acid to the material in S1, dissolving, and stirring for the first time for 4 hours;

[0200] S3, adding the dried ginger essential oil inclusion compound to the solution of S2, and stirring for a second time for 3 hours;

[0201] S4, subjecting the solution stirred in S3 to ultrasonic defoaming to obtain an electrospinning solution.

[0202] Example 3-2

[0203] 2 parts of polyvinyl alcohol; 0.5 parts of hyaluronic acid; 1 part of dried ginger essential oil inclusion compound; 18 parts of water;

[0204] Among them, the dried ginger essential oil inclusion compound adopts the product prepared in Example 2-3.

[0205] S1, adding polyvinyl alcohol into water and heating to dissolve;

[0206] S2, adding hyaluronic acid to the material in S1, dissolving, and stirring for the first time for 6 hours;

[0207] S3, adding the dried ginger essential oil inclusion compound to the solution of S2, and stirring for a second time for 1 hour;

[0208] S4, subjecting the solution stirred in S3 to ultrasonic defoaming to obtain an electrospinning solution.

[0209] Comparative Example 3-1

[0210] 1.5 parts of polyvinyl alcohol; 1 part of hyaluronic acid; 0.4 parts of dried ginger essential oil inclusion compound; 22 parts of water; wherein the inclusion rate of the dried ginger essential oil inclusion compound is 70%.

[0211] S1, adding polyvinyl alcohol into water and heating to dissolve;

[0212] S2, adding hyaluronic acid to the material in S1, dissolving, and stirring for the first time for 4 hours;

[0213] S3, adding the dried ginger essential oil inclusion compound to the solution of S2, and stirring for a second time for 3 hours;

[0214] S4, subjecting the solution stirred in S3 to ultrasonic defoaming to obtain an electrospinning solution.

[0215] Comparative Example 3-2

[0216] 1.5 parts of polyvinyl alcohol; 1 part of hyaluronic acid; 0.4 parts of dried ginger essential oil inclusion compound; 22 parts of water; wherein the inclusion rate of the dried ginger essential oil inclusion compound is 60%.

[0217] S1, adding polyvinyl alcohol into water and heating to dissolve;

[0218] S2, adding hyaluronic acid to the material in S1, dissolving, and stirring for the first time for 4 hours;

[0219] S3, adding the dried ginger essential oil inclusion compound to the solution of S2, and stirring for a second time for 3 hours;

[0220] S4, subjecting the solution stirred in S3 to ultrasonic defoaming to obtain an electrospinning solution.

[0221] Comparative Example 3-3

[0222] 2.0 parts of polyvinyl alcohol; 0.8 parts of hyaluronic acid; 0.4 parts of dried ginger essential oil inclusion compound; 20 parts of water; wherein the dried ginger essential oil inclusion compound is the product prepared in Example 2-1

[0223] S1, adding polyvinyl alcohol into water and heating to dissolve;

[0224] S2, adding hyaluronic acid to the material in S1, dissolving, and stirring for the first time for 5 hours;

[0225] S3, adding the dried ginger essential oil inclusion compound to the solution of S2, and stirring for a second time for 2 hours;

[0226] S4, subjecting the solution stirred in S3 to ultrasonic defoaming to obtain an electrospinning solution.

[0227] Comparative Examples 3-4

[0228] 1.2 parts of polyvinyl alcohol; 0.8 parts of hyaluronic acid; 1.2 parts of dried ginger essential oil inclusion compound; 20 parts of water;

[0229] Among them, the dried ginger essential oil inclusion compound is the product prepared in Example 2-1

[0230] S1, adding polyvinyl alcohol into water and heating to dissolve;

[0231] S2, adding hyaluronic acid to the material in S1, dissolving, and stirring for the first time for 5 hours;

[0232] S3, adding the dried ginger essential oil inclusion compound to the solution of S2, and stirring for a second time for 2 hours;

[0233] S4, subjecting the solution stirred in S3 to ultrasonic defoaming to obtain an electrospinning solution.

[0234] The electrospinning solutions prepared in Example 3-1, Example 3-2 and Comparative Examples 3-1, 3-2, 3-3 and 3-4 were used to prepare nanofiber masks loaded with dried ginger essential oil-cyclodextrin inclusion complex using an electrospinning device, using the process parameters in Table 4.

[0235] The wettability and moisturizing efficacy of the dried ginger essential oil nanofiber mask were tested for the facial masks prepared in Example 3-1, Example 3-2, Comparative Example 3-1, Comparative Example 3-2, Comparative Example 3-3 and Comparative Example 3-4 (the testing method is as shown in Example 3), and the test results are shown in Table 7.

[0236] Table 7

[0237] / Average contact angle (°) Average moisture content (%) PVA-HA-GEO / βCD-2 44.74 44 PVA-HA-GEO / βCD-3 56.90 46 PVA-HA-GEO / βCD-4 61.67 43 Example 3-1 45.33 45 Example 3-2 60.19 44 Comparative Example 3-1 75.32 33 Comparative Example 3-2 78.22 32 Comparative Example 3-3 65.12 34 Comparative Examples 3-4 70.49 36

[0238] The electrospinning solution of the dried ginger essential oil nanofiber mask provided in the present application uses polyvinyl alcohol, hyaluronic acid, dried ginger essential oil inclusion compound and water as raw materials, and controls the inclusion rate of the dried ginger essential oil inclusion compound and the ratio between the various raw materials, so that the nanofiber mask loaded with the dried ginger essential oil inclusion compound prepared by using the electrospinning solution has a smooth surface, a compact structure, good hydrophilicity and wetting properties, high safety and moisturizing properties, and is easy to promote and apply.

[0239] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An electrospinning solution for a dried ginger essential oil nanofiber mask, characterized in that: The following raw materials are prepared by weight: 1.5-2 parts of polyvinyl alcohol; 0.5-1 part of hyaluronic acid; 0.4-1 part of dried ginger essential oil inclusion compound; 18-22 parts of water; Among them, the inclusion rate of dried ginger essential oil inclusion complex is more than 80%.

2. The electrospinning solution of the dried ginger essential oil nanofiber mask according to claim 1, characterized in that: The added mass ratio of the dried ginger essential oil inclusion compound and polyvinyl alcohol is 0.25-0.5:

1.

3. The electrospinning solution of the dried ginger essential oil nanofiber mask according to claim 1, characterized in that: The inclusion rate of dried ginger essential oil inclusion complex is over 83%.

4. The electrospinning solution of the dried ginger essential oil nanofiber mask according to claim 1, characterized in that: The dried ginger essential oil inclusion compound is prepared by the following method: Step 1, slowly dripping the ethanol solution of dried ginger essential oil into the cyclodextrin aqueous solution for reaction, mixing evenly, cooling to room temperature, and refrigerating for standby use; wherein the mass ratio of dried ginger essential oil to cyclodextrin is 1:3.5-4.5; the reaction temperature is 35°C-45°C, and the reaction time is 50-60min; Step 2: centrifuge the material of step 1, and dry and grind the centrifugal precipitate to obtain the dried ginger essential oil inclusion compound.

5. The electrospinning solution of the dried ginger essential oil nanofiber mask according to claim 4, characterized in that: The mass ratio of dried ginger essential oil to cyclodextrin is 1:4-4.

5.

6. The electrospinning solution of the dried ginger essential oil nanofiber mask according to claim 4, characterized in that: In the step 1, the reaction temperature is 40°C to 45°C.

7. The electrospinning solution of the dried ginger essential oil nanofiber mask according to claim 4, characterized in that: In the step 1, the reaction time is 55 to 60 minutes.

8. The method for preparing the electrospinning solution of the dried ginger essential oil nanofiber facial mask according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1, adding polyvinyl alcohol into water and heating to dissolve; S2, adding hyaluronic acid to the material in S1, dissolving it, and performing the first stirring; S3, adding the dried ginger essential oil inclusion compound to the solution of S2, and stirring for the second time; S4, subjecting the solution stirred in S3 to ultrasonic defoaming to obtain an electrospinning solution.

9. A dried ginger essential oil nanofiber mask, characterized in that: The nanofiber mask is prepared by using the electrospinning solution of the dried ginger essential oil nanofiber mask as described in any one of claims 1 to 7.

10. A method for preparing the dried ginger essential oil nanofiber mask as claimed in claim 9, characterized in that: The electrospinning solution was added into the electrospinning equipment at a feeding rate of 0.3-0.5 mL / h and a roller speed of 250-350 r / min.

Citation Information

Patent Citations

  • Hydrophobic nanofiber membrane containing plant essential oil and preparation method and application thereof

    CN104005177A

  • Hyaluronic acid / silk fibroin nano-fibre and preparation method thereof

    CN106676670A

  • Citrus essential oil nanofilm and preparation method thereof

    CN107190422A

  • Preparation method of moisturizing and hydrating nanofiber mask

    CN112587443A

  • Manufacturing method of 3D composite air filtering material

    CN112844060A